Bovine Angptl6 gene effects on growth traits in three Chinese native cattle breeds - LI, AIMIN; LAN, XIANYONG; MA, YUN; LIU, DONG; CAI, HANFANG; LE, CHUZHAO; CHEN, HONG (The Indian Journal of Animal Sciences, 2012)
As a circulating orphan peptide secreted by liver, Angptl6 gene might have great effects on growth and development of animals. The objective of this study was to explore sequence variants (SVs) of Angptl6 and to analyze their associations with growth traits in 737 individuals belonging to 3 Chinese native cattle. Herein, 3 variants were revealed by DNA pools sequencing and PCR-RFLP (or ACRS-PCR-RFLP) methods. These SVs were located at nt 2359, nt 2403 and nt 3258 (viz. SV1, SV2, SV3) respectively. All the analyzed populations were at Hardy-Weinberg equilibrium by c2-test. The linkage disequilibrium (LD) and haplotype analyses of 3 SVs revealed 8 different haplotypes. Thereinto, 2 dominant haplotypes (TCG and CCG) occurred with a frequency of 63.17% and 18.67% respectively. Association analysis showed the SV1 was significantly associated with BLI-6, and the SV2 and SV3 were significantly associated with CGI-24 and BHI-6 of individuals of Nanyang breed respectively. Further, combined SVs analysis revealed the ADG-18 of individuals with diplotype TC-CC-GG was higher than other combined genotypes in SV1-SV2-SV3 locus. Moreover, CG-18 with TC-GG and ADG-18 with TT-GT were preponderant in SV1-SV3 locus. Thus, 3 SVs showed great comprehensive effects on growth traits of Nanyang cattle, which indicated that they could be contributed to genetic and breeding programmes in cattle. Although there was no sufficient evidence these SVs greatly effect on the growth traits of cattle, the significant effects of these variants with these parameters could not be ignored.